PROFESIONALISME AUDITOR, PENGALAMAN AUDITOR, PEMAHAMAN GOOD GOVERNANCE, DAN KUALITAS AUDIT - Wahyuni, Mirra Sri; Irwansyah, Irwansyah; Baihaqi, Baihaqi (UNIB Press, 2016)
The purpose of this research is to ditermine the influence of Professionalism, Experience, Understanding of Good Governance of Bengkulu Auditor to the audit quality in financial supervision. As the samples used in this study is the Inspectorate Offices of Bengkulu Province. While the data analysis was conducted on the data obtained from the questionnaires of 60 respondents who served as auditor.The data analysis results show that the Professionalism, Experience, and Good Governance have positive influence on auditing quality of auditor at Bengkulu Province Inspectorate.The research finding can be used as positive recomandation for input to further enhance of professionalism, experience and the good governance understanding in order to improve to be higher quality audit by auditor of Inspectorate of Bengkulu Province.